Surface Tension of Sugarcane Juice - Jain, P C; Anwar, S I (Journal of Agricultural Engineering, 2003)
Sugarcane juice is a popular drink. Aerating it with oxygen or some other gases may help in improving its taste and keeping quality. It is in this context that the knowledge of surface tension of sugarcane juice would be required in the design of a gas liquid aerator for aerating the juice. When a fluid is sparged with air, its surface tension during aeration would influence the interfacial area available for gas mass- transfer. Surface tension measurements also provide an indication of how foamy a liquid may be.